Getting Out Early: An Analysis of Market Making Activity at the Recommending Analyst's Firm - JUERGENS, JENNIFER L.; LINDSEY, LAURA (Journal of Finance, 2009)
ABSTRACT This paper examines trading volume for Nasdaq market makers around analyst recommendation changes issued by an analyst at the same firm. Using Nasdaq PostData, we find a disproportionate increase in market making volume associated with the firm's recommendation changes and evidence of elevated sell volume at the recommending analyst's firm in the 2 days preceding a downgrade. The implications are that the information source matters in determining the placement of trades and that the issuing analyst's firm appears to be rewarded for prereleasing information through increased volume. These findings constitute new evidence of compensation for research production through the market making channel.